Performance Evaluation of Three Different Inverter Configurations of DVR for Mitigation of Voltage Events - Miska Prasad; Ashok Kumar Akella (IAES Indonesian Section, 2016)
The voltage events namely voltage sags and voltage swells represent the most common, frequent and important power quality events in today’s power system. Dynamic voltage restorer (DVR) is one of the key components used to mitigate the supply voltage quality disturbances in terms of voltage sags and swells in the distribution system. It consists of an energy storage unit, a voltage source inverter, a filter, a coupling transformer and the control system. This paper presents three different inverter configurations of dynamic voltage restorer (DVR) for mitigation of voltage events such as voltage sags and swells with sudden addition or removal of the nonlinear load. These three configurations are voltage source inverter based DVR (VSI-DVR), current source inverter based DVR (CSI-DVR) and impedance or Z-source inverter based DVR (ZSI-DVR). The d-q control technique is used to control the operation of the DVR. The response of ZSI-DVR for mitigation of voltage sags and swells are investigated and compared with VSI-DVR and CSI-DVR using MATLAB/SIMULINK environment.